Pengembangan media kartu karier untuk meningkatkan pengambilan keputusan karier siswa - Andini, Aulia Prima; Ilahi, Fauzi Nur; Almuin, Nani (Universitas Indraprasta PGRI, 2024)
the method used in this research uses the Research and Development (RnD) development method based on the theory of Borg and Gall (1983). The research produced a product in the form of a career card through three stages of assessment and revision which resulted in a Media Expert of 87.50%, a BK Material Expert of 92.19%, and a Language Expert of 90% with a score category of